Peningkatan Hasil Belajar IPA Siswa SMP Menggunakan Model Pembelajaran Teams Games Tournament - Martina Munda (Jurnal Didaktika Pendidikan Dasar, 2023)
This research aimed to improve the science learning outcomes through the Teams Games Tournament (TGT) learning model of theeightgradeclass students. The research method was Classroom Action Research (CAR) which consisted of four phases such as: planning, action, observation, and reflection. The research procedure contained two (2) cycles in which each cycle consisted of three meetings. Data was collected through written learning outcomes tests that were conducted at the end of every cycle. Data then was analyzed using a quantitative descriptive method. The result showed that numbers of students who were complete in learning increased gradually from 18 students in the first cycle to 25 students in the second cycle. The percentage of classical learning completeness increased steadily from 72 % in the first cycle to 100 % in the second cycle or there was an increase by 28 %. Likewise, the class average score went from 82,2 in the first cycle up to 94,2 in the second cycle or there was an increase up to 12 points. The lowest score in pre-cycle was 35, and this score gradually rose to 60 in the first cycle and 75 in the second cycle. In conclusion, the Teams Games Tournament (TGT) learning model might increase the science learning outcomes of the class VIIIB students of Sint Antonius PaduaSasiCatholic Junior High School.